ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE EDUCATION: A NEW ERA OF LEARNING - Yangiboyeva Iroda To’lqin Kizi (DEVELOPMENT OF EDUCATION AND SCIENCE IN THE ERA OF DIGITAL TRANSFORMATION, 2025)
The rapid digital transformation of education has brought Artificial Intelligence (AI) to the forefront of English language teaching and learning. This paper explores the role of AI in reshaping traditional instructional practices, emphasizing its ability to personalize learning, provide instant feedback, and enhance learner engagement. By analyzing widely used AI-based platforms such as ChatGPT, Grammarly, Duolingo Max, and Elsa Speak, the study highlights how technology supports language acquisition through adaptive and interactive methods. The paper also discusses the challenges associated with AI integration, including ethical concerns, data privacy issues, and the potential reduction of human interaction in classrooms. Furthermore, it examines the evolving role of teachers in AI-supported classrooms and proposes strategies for effective integration. The findings suggest that a balanced combination of AI tools and human expertise can create a more inclusive, effective, and learner-centered environment in the era of digital transformation.